2008
DOI: 10.1007/s10238-008-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of methylenetetrahydrofolate reductase and methionine synthase genes and bladder cancer risk: a case–control study with meta-analysis

Abstract: Folate deficiency due to the methylenetetrahydrofolate reductase (MTHFR) and methionine synthase (MS) variants leads to carcinogenesis by affecting DNA synthesis, repair, and methylation. We hypothesized that the MTHFR C677T, A1298C, and MS A2756G polymorphisms are associated with risk of bladder cancer. In a case-control study of 239 bladder cancer cases and 250 cancer-free controls, we found that the MTHFR 677TT genotype was statistically significantly associated with an increased risk of bladder cancer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
2
15
1
Order By: Relevance
“…Their meta-analysis indicated that the MTHFR C677T polymorphism was not associated with bladder cancer risk, which was consistent with our findings. However, Wang et al [17] in their own study found an increased risk effect for 677T allele on risk of bladder cancer which is in contrary with our results and published data in literature. There is significant heterogeneity for MTHFR gene polymorphisms among the different populations.…”
Section: S404contrasting
confidence: 99%
See 2 more Smart Citations
“…Their meta-analysis indicated that the MTHFR C677T polymorphism was not associated with bladder cancer risk, which was consistent with our findings. However, Wang et al [17] in their own study found an increased risk effect for 677T allele on risk of bladder cancer which is in contrary with our results and published data in literature. There is significant heterogeneity for MTHFR gene polymorphisms among the different populations.…”
Section: S404contrasting
confidence: 99%
“…The novel MTHFR 1793A variant is rare in Caucasians, and the allele frequency in our study population was consistent with that reported by Rady et al [16]. Wang et al [17] performed a meta-analysis on the effect of polymorphism in MTHFR gene and bladder cancer risk. They analyzed seven published literatures.…”
Section: S404supporting
confidence: 91%
See 1 more Smart Citation
“…A total of 11 studies (57,1821,23,2527) were included in this meta-analysis for Ala222Val (including 3,463 cases and 3,.927 controls) and 9 studies (57,1921,23,25,27) were included for Glu429Ala (including 3,177 cases and 3,502 controls) (Table I). Three of the 11 studies were population-based and eight were hospital-based studies.…”
Section: Resultsmentioning
confidence: 99%
“…Using a similar approach, other investigators have identified pooled effects of folate-related genes on cancer risk. 39,40 The approach of canvassing genetic variants in implicated biological pathways to generate cumulative risk scores holds promise in resolving the so-called ''missing heritability'' in schizophrenia and other complex genetic disorders in psychiatry 41 -just as in the present study, where the net effects of folate-related variants outweighed the influence of MTHFR 677C>T alone on negative symptom severity.…”
mentioning
confidence: 84%